EFEKTIVITAS PEMBERIAN EKSTRAK DAUN SIRSAK (ANNONA MURICATA LINN) TERHADAP KEJADIAN KEPUTIHAN PATOLOGIS PADA WANITA USIA SUBUR: Effectiveness Of Granting Of Sirsak Leaf Extract ( Annova Muricata Linn) On The Event Of pathological Derivity In Subur Aged Woman - TUTIK TUTIK HIDAYATI (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2020)
The problem of vaginal discharge is a problem that has long been a problem for women, especially in women of childbearing age who do not know much about vaginal discharge and do not care about the problem. Though leucorrhoea can be very fatal if it is slowly handled (Rozi, 2013). Generally women who suffer from leucorrhoea secrete too much and cause an unpleasant odor. Research in East Java shows that 75% of women experience vaginal discharge at least once in a lifetime, and 45% can experience vaginal discharge twice or more (Aini, 2014). Pathological vaginal discharge data in Probolinggo District was 1.91% in 2014. Based on a preliminary study conducted on January 29, 2017 by taking secondary data from 44 patient visits, which experienced pathological vaginal discharge as many as 32 people at Pajarakan Health Center in 2016 and data pathological leucorrhoea in Pajarakan Community Health Center in January and February 2017 as many as 4 people. Characteristics of causes of vaginal discharge (fluor albus) in women of childbearing age such as age, marital status, parity, educational status, employment status. The purpose of this study was to determine the effectiveness of soursop leaf extract (Annona muricata Linn) on pathological vaginal discharge in women of childbearing age. This study used a quantitative research method approach. this study uses a prospective cohort. Population: All women of childbearing age who have pathological leucorrhoea at Pajarakan Community Health Center, Pajarakan Subdistrict, Probolinggo District, from January to December 2016 were 32 respondents. Data collection techniques with questionnaires, observation sheets (checklist), SOP. The results of the study were obtained with the Mann Whitney statistical test to get a value ? value = 0,000, which means smaller than ? 0.05 so that there is effectiveness in the administration of soursop leaf extract (Annona muricata Linn) on the incidence of pathological vaginal discharge in women of childbearing age in Pajarakan Health Center, Pajarakan District Probolinggo.